Alginate biopolymers: Counteracting the impact of superabsorbent polymers on mortar strength. (1st May 2016) - Mignon, Arn; Snoeck, Didier; D'Halluin, Kenny; Balcaen, Lieve; Vanhaecke, Frank; Dubruel, Peter; Van Vlierberghe, Sandra; De Belie, Nele
Highlights: CaAlg exhibits a strong moisture uptake capacity especially at air RH. NaAlg becomes insoluble in mortar due to the divalent cations present in CF. CaAlg leads to only a small compression strength reduction <15% upon 1 m% addition. All alginates except NaAlg 1 m% meet the strength demand of 52.5 MPa at 28 days. Alginate can be considered a very promising material in concrete applications. Abstract: Synthetic superabsorbent polymers (SAPs) are used in concrete for various applications. However, the addition of SAPs may lead to a significant decrease in mortar strength. In order to overcome this bottleneck, the present work focuses on the application of biopolymers as SAPs, more specifically polysaccharides including both uncross-linked sodium alginate as well as physically cross-linked calcium alginate. Interestingly, results indicate no or a limited (i.e. < 15%) reduction in strength upon introducing 1% relative to cement mass. Alginate can therefore be considered a promising material, not only for internal curing but even when high SAP amounts are required.